Historical dictionary of the League of Nations - Ginneken, Anique H. M. van, 1946-2015 (Historical dictionaries of international organizations series ;, 2006)
Created in 1919, shortly after World War I, the League of Nations was principally designed to put an end to war. But it went into hibernation when World War II broke out, and was formally wound up in 1946. Not having achieved its primary objective, it wasdeemed a failure. However, the many accomplishments it did realize certainly allows for arguments against this idea. During its two-decade existence, the League of Nations resolved and defused many conflicts and crises, as well as established a rapport among its members. It was also active in many other political, social, and technical fields.